Professional ecologies shaping technology adoption in early childhood education with multilingual children. (28th March 2019) - Davis, Niki; Harris, Leona; Cunningham, Una
Abstract: Strategic deployment of the digital world in educational ecosystems inhabited by multilingual children (4–6 years old), their teachers and their families is evolving in some communities. This study reveals the "actors" and communities that mediate the extent and the nature of engagement with new media in contexts of early childhood education, including evidence of partnership with teachers. Teachers and parents were found to be the "keystone species, " with the teacher the most influential mediator for young multilingual children. Empirical research into the interacting learning ecologies of young children in six early childhood centres and five associated schools is based on interviews with teachers and families plus photographs of the linguistic landscapes in these physical and digital ecosystems. Fragmented multiple perspectives on the education of young children and technology adoption are brought together with Davis' Arena Framework of change with digital technologies in education. One early childhood education centre is mapped in a global arena to expose the co‐evolution of education with technology that occurs in all levels, local through global. This clarifies the need for co‐construction of policy and practice in these ecosystems so that that emergent bilinguals can have a better start in the digital world.